Phosphate starvation induces uptake of glyphosate by Pseudomonas sp. strain PG2982. - Fitzgibbon, J (1988)
Pseudomonas sp. strain PG2982 has the ability to use the phosphonate herbicide, glyphosate, as a sole phosphorus source (J. K. Moore, H. D. Braymer, and A. D. Larson, Appl. Environ. Microbiol. 46:316-320, 1983). Glyphosate uptake is maximal in the late log phase of growth and is induced by phosphate starvation. Uptake is inhibited by phosphate and arsenate, but not by the amino acids glycine and sarcosine. The Km and Vmax for glyphosate uptake were calculated to be 23 microM and 0.97 nmol/mg (dry weight) per min, respectively. A phosphate transport system with a broad substrate specificity may be responsible for glyphosate uptake.